High Colchicine Doses Are Really Silver Bullets Against COVID-19 - Mitev V. (Acta Medica Bulgarica)
The numerous attempts to prove a therapeutic effect of low-dose colchicine for the treatment of Coronavirus disease-2019 (COVID-19) have been discouraging. Increase of doses, however, leads to accumulation in leukocytes and inhibition of the cytokine storm thus preventing COVID-19 complications and hospitalizations. Hospital mortality drops up to 7-fold, while outpatients practically do not reach hospitalization.